The Impact of Mobile Phone Use on Adolescent Health - Carvalho Feitosa, Antônio Gelcivan; Ribeiro da Silva, Márcio; Nery de Souza Ferreira, Matheus; Pereira Gonçalves, Bruno; Lobo de Oliveira, Jean Mark; Pereira Gomes, Rilmar; Barbosa de Alencar, David (International Journal for Innovation Education and Research, 2019)
With the increasing rise of smartphones among adolescents, the question arose about the impact of the use of mobile phones among this audience, seeking to assess the harms caused by their excessive use. The present work was elaborated through bibliographical research in articles, books and websites, in a non-systematic way through qualitative and quantitative research, analyzing printed questionnaire. Regarding the results related to the problems caused by the use of smartphones, such as lack of attention, indisposition, poor school performance, little interaction in the classes kept an average of 22.5% difference for those who felt affected, about the posture we have a relatively few. high, however, is still less than half of respondents, but only 33.75% of people who do not worry about posture when using the phone showing, therefore, that young people, focus of our research, has a good ergonomic behavior , both when using the smartphone and watching classes, picking up objects on the floor, and sitting in the chair.